Labial Cartilaginous Choristoma Mimicking a Mucocele: A Rare Case Report and Literature Review - Kimia Hafezimotlagh; Saede Atarbashi‐Moghadam; Ali Lotfi; Bahram Ardalani; Mohammadreza Kashefi Baher (Clinical Case Reports, 2026)
ABSTRACT Choristomas are non‐neoplastic, tumor‐like lesions composed of histologically normal tissue in ectopic locations, though their exact pathogenesis remains unknown. Labial cartilaginous choristoma is an exceptionally rare benign lesion that clinically mimics common lip swellings, posing a diagnostic challenge. A 25‐year‐old male presented with a painless, slow‐growing submucosal swelling of the right lower labial mucosa, measuring 1 cm in diameter, that had been present for 2 years. Clinical examination revealed a firm, mobile, pink nodule with an intact overlying mucosa and focal hyperkeratosis, without associated trauma or relevant medical history. The differential diagnoses included mucocele and focal fibrous hyperplasia. Following excisional biopsy, histopathologic examination with hematoxylin and eosin staining demonstrated a well‐defined lesion composed of mature cartilaginous tissue admixed with fibrous and adipose elements, devoid of cytological atypia, confirming the diagnosis of cartilaginous choristoma. Complete surgical excision was diagnostic and associated with an excellent clinical outcome. A review of the literature identified 12 previously reported cases of labial choristoma, with the cartilaginous type predominating (53.85%), a slight female predilection (F:M ratio 1.17), and most presenting as asymptomatic swellings. No recurrence has been documented following adequate excision at the labial site. This case highlights that labial cartilaginous choristoma, though rare, should be considered in the differential diagnosis of persistent lip swellings, as definitive diagnosis relies on histopathologic evaluation, and complete surgical excision appears curative.